Agriculture Sector and Agribusiness Entrepreneurship Potential in Kazakhstan: A SWOT-TOWS Analysis - TATIKOVA, Asiya; BAITILENOVA, Yerikkul; NARENOVA, Ayman; KALDYGOZOVA, Meruert; KAZHIEVA, Zhaniya; DZHAAMBAYEVA, Bakhtugul; AKTYMBAYEVA, Aliya (Journal of Advanced Research in Law and Economics; Vol 10 No 8 (2019): JARLE Volume X Issue 8(46) Winter 2019, 2019)
Agribusiness entrepreneurship has significant role in the economy to foster rural development in the country. Kazakhstan has strong potential for the development of agribusiness entrepreneurship due to country’s considerable land resources, as Kazakhstan has the world’s 12 th largest arable land area, and fifth in the world in terms of pastureland of 182.2 million hectares, but it uses only about 30% of the pastures. The current agribusiness entrepreneurship in Kazakhstan are mainly in the nature of food processing units. They have implication on food security and basic needs of human being. The present article aims at identifying strengths, weaknesses, opportunities, and threats for agribusiness entrepreneurship with combining financial and economic aspects in Kazakhstan. This research proposes among others effective and adequate agribusiness entrepreneurship policies such as price stabilization policy and programmes for addressing factors that hinder the growth and development of agribusiness entrepreneurship in Kazakhstan.